2020
DOI: 10.1167/iovs.61.8.18
|View full text |Cite
|
Sign up to set email alerts
|

Spasm of Near Reflex: Objective Assessment of the Near-Triad

Abstract: To characterize binocular steady-state accommodation, pupil and convergence responses (near triad) in spasm of near reflex (SNR) before and after optical and pharmacological intervention. To identify the putative source of SNR in the neural control schema of accommodation-vergence interaction using controls-engineering modeling. METHODS. Near-triad of 15 patients with SNR (9 to 23 years) was recorded using an infrared photorefractor at 2m viewing distance for 120s during clinical presentation, after optical fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…If a post-cycloplegic spasm develops, the author suggests using a modified fogging technique to improve accommodation stability and visual acuity. 8 Roy et al suggested using the modified optical fogging method or one-time cycloplegic drops to evaluate actual refractive error and alleviate the near reflex spasm. In a cohort study, the author treated 66% of patients with mild spasm of the near reflex, 22% of patients with moderate spasm of the near reflex, and 13% of patients with severe spasm of the near reflex.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…If a post-cycloplegic spasm develops, the author suggests using a modified fogging technique to improve accommodation stability and visual acuity. 8 Roy et al suggested using the modified optical fogging method or one-time cycloplegic drops to evaluate actual refractive error and alleviate the near reflex spasm. In a cohort study, the author treated 66% of patients with mild spasm of the near reflex, 22% of patients with moderate spasm of the near reflex, and 13% of patients with severe spasm of the near reflex.…”
Section: Methodsmentioning
confidence: 99%
“…3,32 Three studies compared the modified optical fogging technique with cycloplegic refraction and applied it as a method to stop the accommodative spasm when it was noticed after post-cycloplegic refraction. 8,36,38 The method involves requiring the patient to perform a close task while stabilising the patient's visual acuity and retinoscopy reflex. Satgunam reports that the two patients diagnosed with accommodative spasm after cycloplegic refraction used the modified optical fogging method to immediately relieve the spasm.…”
Section: Assessment and Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…When fixation switches from a distant object to a near object, the near-reflex response, including ocular accommodation, convergence and pupil contraction, is elicited to achieve and maintain clear single-binocular vision [ 8 ]. When changing our focus from a near target to a distant target, the reverse response occurs, including ocular disaccommodation, divergence and pupil mydriasis.…”
Section: Introductionmentioning
confidence: 99%